Jewish Religious Life in Lithuania in the 18th-20th Centuries - Lempertienė, Lara,; Stampfer, Shaul,; Wodzinski, Marcin, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
This volume attempts to address the complicated issue of distinctive characteristics of Jewish religious life in Lithuania. Its authors and editors deal with the range of religious expressions, with the religious life of different sectors of the Jewish community of Lithuania and with the dynamics of change in religious life in Lithuania over time. In this volume, Lithuania is more a historical and social concept than a geographical territory with clearly delineated borders and political identity. The authors deliberate how "Lithuanian" are the religious phenomena they discuss and what the historical agents understood as Lithuania in their given period, area, and historical circumstances.